PERDAMAIAN DALAM KITAB SUCI AGAMA-AGAMA - Ardiansyah, Wahyu (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2025)
Among the human traits is the love of peace and tranquility. Some people are willing to do anything to seek tranquility and peace in their lives. So, peace is a global vision of mankind in the world. In order to maintain world peace, the United Nations was born and formed. Before humans realized the importance of peace, religions had taught and advised humans about the conception of peace. Religions in Indonesia with their respective holy books are very instrumental in creating peace in a pluralistic and multicultural Indonesian society. However, the role of religion is very dependent on the understanding, appreciation and practice of religious teachings of its adherents. A good understanding of the conception of peace in the holy book will result in the appreciation and practice of these values in society. Knowledge of the conception of the teachings of other religions also helps in building tolerance and egalitarian principles in the lives of religious believers in Indonesia. It is on this basis that this research was conducted, to uncover and encompass some of the conceptions of peace teachings in the holy books of religions in Indonesia. Based on these holy books, this research was conducted.